The use of the farm accountancy data network for estimation of the optimal family farm size according to the microeconomic theory - Baležentis, Tomas; Valkauskas, Romualdas (Buhalterinės apskaitos teorija ir praktika, 2014)
Benchmarking of the economic subjects—viz. enterprises, organizations, regions—usually involves assessment of the efficiency. Suchlike analyses are not only important in the private sector, but also in the public one for public agencies are usually funded by public funds and thus need to be effective. Indeed, the private (business) subjects are sometimes also operating under the environment requiring appropriate regulation based on benchmarking. This is the case for the agricultural sector which receives voluminous public support as direct payments and rural development measures. On the other hand, the efficiency of agricultural sector impacts the prices of agricultural products as well as factor markets. Therefore, it is important to measure the efficiency of agricultural sector as an outcome of the effectiveness of the agricultural policy. The scale efficiency constitutes one of the components of the gross technical efficiency. The latter measure is related to the farm size and farm structure in general. Furthermore, the optimal farm size is a key issue for the agricultural policy and thus is often influenced by the legal regulations. This paper aims at identifying the optimal scale size for Lithuanian family farms. The paper discusses the neoclassical methodology for analysis of the scale efficiency. The results indicate that the optimal farm size depends on the farming type. Nevertheless, the current maximum limit of land area (i. e. 500 ha) has not been exceeded by any farming type.